Indian Interpretation of the Bible: Festschrift in honour of Prof. Dr. Joseph Pathrapankal, cmi - Editors, Review (Journal of Dharma, 2000)
Augustine Thottakara (ed.), Indian Interpretation of the Bible (Festschrift in honour of Prof. Dr. Joseph Pathrapankal, cmi), Bangalore: Dharmaram Publications, 2000, pp. 492, Rs. 350.00, US$22.00, ISBN: 81-86861-27-0